2020
DOI: 10.3390/rs12010148
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Streaklines as Recorders of Synoptic Flow Direction in a Deltaic Setting

Abstract: Knowledge of the flow patterns within distributary systems is key for understanding deltaic hydro- and morpho-dynamics, yet synoptic measurements of flow fields remain virtually nonexistent. As a means of overcoming this problem, a small number of studies have used biogenic surface films as synoptic flow tracers, under the assumption that biofilm streaklines are tangent to the local flow direction. Here we rigorously test this assumption and show that, despite flow patterns that change severely in space and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 26 publications
(33 reference statements)
3
21
0
Order By: Relevance
“…This is consistent with Cathcart et al. (2020), who found that under low river discharge, rising tide inhibited streaklines. Additionally, for the October 17 flight, diffuse regions of high SSC in island interiors could be a consequence of wave‐driven sediment resuspension.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with Cathcart et al. (2020), who found that under low river discharge, rising tide inhibited streaklines. Additionally, for the October 17 flight, diffuse regions of high SSC in island interiors could be a consequence of wave‐driven sediment resuspension.…”
Section: Discussionsupporting
confidence: 93%
“…Tidal cycle may play a role; the October 17 flight was during a period of rising tide, whereas the October 18 flight with visible streaklines took place near the end of a long period of falling tide (Figure S2 in Supporting Information S1). This is consistent with Cathcart et al (2020), who found that under low river discharge, rising tide inhibited streaklines. Additionally, for the October 17 flight, diffuse regions of high SSC in island interiors could be a consequence of wave-driven sediment resuspension.…”
Section: Discussionsupporting
confidence: 92%
“…By interpreting the divergence of the flow direction field, the location of subaqueous channel tips can be estimated from streaklines (Shaw et al, ). The resolution produced by these new techniques is low compared to direct altimetry, and ideal hydrodynamic conditions are required (Cathcart et al, ). Even so, the shallow coastal zone on river deltas is vast and difficult to measure, so the systematic use of these techniques has the potential to significantly improve coastal DEMs.…”
Section: Potential Resilience Analysis Toolsmentioning
confidence: 99%
“…Due to its small size, relatively good historical record over the last several decades, and lack of substantial engineering [47], the WLD is an ideal place to study young delta dynamics at sub-decadal scales. The WLD has proven useful in previous geomorphological studies, such as on sediment diversion and marsh restoration potential [12,[51][52][53][54][55], (sub)aqueous sediment and channel dynamics and fluxes [56][57][58][59][60][61][62][63], river flood, hurricane, and cold front effects on marsh elevations [5,64,65], and delta sedimentation and lobe progradation [18,66]. The WLD has also yielded insights into delta hydrology, including on surface water residence and connectivity [67][68][69][70], surface water-groundwater interactions [31], and effects of river, floods, tides, wind, hurricanes, and cold fronts on water levels [4,5,31,50,64,65,71,72].…”
Section: Study Areamentioning
confidence: 99%